Foldable Denture: For Microstomia Patient - Sandeep Kumar; Aman Arora; Reena Yadav (Case Reports in Dentistry)
Microstomia may result from surgical treatment of orofacial neoplasms, cleft lips, maxillofacial trauma, burns, radiotherapy, or scleroderma. A maximal oral opening that is smaller than the size of a complete denture can make prosthetic treatment challenging. This clinical paper presents the prosthodontic management of a total edentulous patient with microstomia. Sectional mandibular and maxillary trays and foldable mandibular and maxillary denture were fabricated for the total edentulous patient.